Spatial distribution of attack of coffee berry borerin conilon coffee - Oliveira e Silva, Bruno Sérgio; Thomazini Herzog, Thaisa; da Silva, Marcelo Barreto; Gontijo, Ivoney; Partelli, Fábio Luiz (Coffee Science - ISSN 1984-3909, 2017)
Insect spatial distribution allows concentrate sampling and management efforts in places with the highest population densities, and insect spatial behavior provides information about conditions in agroecosystem and migration or plague aggregation. Despite the importance for pest management, spatial distribution knowledge of Hypothenemus hampei in conilon coffee has been rare reported. An irregular mesh with 100 sampling points was installed in a high yield crop located in the municipality of São Mateus, Espírito Santo State, Brazil (2011/2012 and 2012/2013 harvests) aiming to determine the incidence of coffee berry borer and its spatial variability in conilon coffee. Fruit samples were collected at each point, and evaluated the number of damaged fruits by checking drilling in each one. The data were submitted to geostatistics analysis. It was possible to check the insect damage density of variability in different harvest years. The semivariograms related to insect damage were better adjusted to spherical and exponential models with spatial dependence index of 72 and 62%, respectively. Atendency of insect attack movement of a harvest to another from the edges to the crop center was observed.